Collaborative Information Seeking The Art and Science of Making the Whole Greater than the Sum of All - Shah, Chirag; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Today$1 (Bs complex, information-intensive problems often require people to work together. Mostly these tasks go far beyond simply searching together; they include information lookup, sharing, synthesis, and decision-making. In addition, they all have an end-goal that is mutually beneficial to all parties involved. Such (3z(Bcollaborative information seeking(3y (B(CIS) projects typically last several sessions and the participants all share an intention to contribute and benefit. Not surprisingly, these processes are highly interactive. Shah focuses on two individually well-understood notions: collaboration and information seeking, with the goal of bringing them together to show how it is a natural tendency for humans to work together on complex tasks. The first part of his book introduces the general notions of collaboration and information seeking, as well as related concepts, terminology, and frameworks; and thus provides the reader with a comprehensive treatment of the concepts underlying CIS. The second part of the book details CIS as a standalone domain. A series of frameworks, theories, and models are introduced to provide a conceptual basis for CIS. The final part describes several systems and applications of CIS, along with their broader implications on other fields such as computer-supported cooperative work (CSCW) and human-computer interaction (HCI). With this first comprehensive overview of an exciting new research field, Shah delivers to graduate students and researchers in academia and industry an encompassing description of the technologies involved, state-of-the-art results, and open challenges as well as research opportunities.s
Part I Introduction -- Introduction -- Collaboration -- Collaborative Information Seeking (CIS) in Context -- Part II Conceptual Understanding of CIS -- Frameworks for CIS Research and Development -- Toward a Model for CIS -- Part III CIS Systems, Applications, and Implications -- Systems and Tools for CIS -- Evaluation -- Conclusion -- Ten Stories of Five Cs -- Brief Overview of Computer-Supported Cooperative Work (CSCW) -- Brief Overview of Computer-Supported Collaborative Learning (CSCL) -- Brief Overview of Computer-Mediated Communication (CMC).
Keywords: Computer science; Database management; Computer Science; Database Management; Computers and Society; Communication Studies